The Effect of Motivation, Workload, and Work Stress on Employee Performance at PT. Permata Karya Jasa - Dhio Pradipta; Utama Zahera Utama; Jubery Marwan (Journal of Center for Energy Policy and Human Resources Capacity Development, 2025)
The purpose of this study is to evaluate the impact that Motivation, Workload, and job stress have on the performance of an organization, both on their own and also in combination. In this study, a descriptive method is used in conjunction with a correlational design, and a quantitative approach is utilised to analyse the data for the purpose of selecting personnel from PT Permata Karya Jasa to serve as research participants—a non-probability sampling approach known as Saturated Sampling was utilised. Validity and reliability tests, descriptive analysis, and inferential statistical analysis are all included in the study, and the data are processed using the SPSS 25.0 software. According to the findings, Motivation has a significant impact on the performance of the organization, while Workload and stress at work also have a substantial effect on performance. Furthermore, when taken into consideration, the factors of Motivation, Workload, and stress at work all have an impact on the performance of the organization simultaneously. As a result of these findings, the essential aspects that influence performance in the workplace have been brought to light, and valuable insights have been provided for future research on how to improve the performance of companies and the well-being of their employees.